A hollow porous microsphere and its preparation method and application
Through the reaction of isocyanate with polyethylene glycol and hydroxyl-containing functional monomers, combined with self-emulsification-self-polymerization technology, hollow porous microspheres with high loading and magnetic content were prepared, which solved the problem of poor pore making effect of polyurethane hollow microspheres and improved their performance in biological applications.
Patent Information
- Application Number
- CN202411897140.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-12-23
AI Technical Summary
In the prior art, the pore-making effect of polyurethane hollow microspheres is poor, and the morphology and size are difficult to control, which affects its performance in biological applications.
Prepolymers are obtained by reacting isocyanate and polyethylene glycol in a solvent, and then reacting with hydroxyl-containing functional monomers to form aqueous polyurethane, and mixed with polymeric monomers, pore-generating agents and initiators to obtain hollow porous microspheres through self-emulsification-autopolymerization reaction.
It has achieved efficient preparation of hollow porous microspheres, with high loading and magnetic content of coupled macromolecules, and is suitable for applications such as chemiluminescence immunodiagnosis, cell sorting and nucleic acid purification.
Smart Images

Figure CN119371604B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biological protein separation, and in particular to a hollow porous microsphere and a preparation method and application thereof. Background Art
[0002] Hollow porous microspheres are tiny particles with many small holes on the shell surface and cavities inside. They are usually made of polymer materials or inorganic materials. These hollow porous microspheres have many unique characteristics: 1) They have a large specific surface area. Due to the large number of microscopic pores and defects inside, these micropores can provide additional surface area, thereby increasing the loading capacity of active substances. 2) They have good mesoporous properties. The pore structures of different sizes, shapes and connectivity give these microspheres adjustable pore size distribution characteristics. By adjusting the preparation conditions or adding appropriate components, different mesoporous structures and size ranges can be achieved. 3) They have low density and good controllability. Because they are full of small pores and cavities inside, this material usually has a low density, and low density brings good buoyancy and dispersibility. 4) They have excellent adsorption and storage capabilities and can adsorb, store and release gas, liquid or solid substances. These unique characteristics make porous hollow microsphere materials show great application prospects in the fields of catalysis, drug delivery and energy storage.
[0003] Microspheres are divided into four categories: 1) Inorganic microspheres represented by silica gel microspheres; 2) Non-degradable polymer microspheres represented by polystyrene, polyurethane, polyacrylate, polymethyl methacrylate, polyacrylamide, etc., and a small amount of degradable polymer microspheres; 3) Organic-inorganic composite microspheres represented by polystyrene / silica magnetic microspheres; 4) Natural polymer microspheres such as agarose, chitosan, albumin, or polyester biodegradable polymer microspheres prepared from polymer raw materials, such as polylactic acid, PLGA, polycaprolactone, and polyurethane.
[0004] There are two main approaches to prepare polyurethane microspheres at present. One is to prepare polyurethane material microspheres by spray drying, flocculation and other methods using existing polyurethane polymers, and the other is to directly polymerize monomer compounds to generate polymer microspheres. At present, the second approach is often used to prepare polyurethane microspheres. Usually, polyol compounds and catalysts are mixed first, and then the mixture is dispersed in the water phase, and then isocyanate compounds are added. Isocyanate compounds gradually diffuse into the dispersed phase in the water phase, react with polyol compounds in the dispersed phase, and form polymer compounds, thereby forming polyurethane microspheres. CN108192074 discloses a method for preparing cross-linked polyurethane microspheres and / or hollow polyurethane microspheres, which mixes hydrophilic polyisocyanates, polyisocyanate monomers, polyether polyols and / or polyester polyols, and catalysts, then adds water, self-emulsifies to form oil-in-water and / or water-in-oil-in-water suspensions, and performs polymerization to obtain cross-linked polyurethane microspheres and / or hollow polyurethane microspheres. However, the patent does not show that the obtained hollow polyurethane microspheres are pore-forming. Although polyurethane porous microspheres can be prepared by selecting different monomers, porogens and polymerization methods to obtain porous microsphere structures. The commonly used methods for preparing porous hollow microsphere morphology are mainly through template method and spray method, while the traditional soft template method requires the addition of additional components such as emulsifiers and stabilizers. These components are easily adsorbed on the microsphere pores and surfaces and are difficult to remove. There is a great risk of affecting the positive detection rate and nonspecific adsorption in subsequent applications such as protein purification and immunodiagnosis; the hard template method requires acid-base treatment or calcination to remove the template, which causes great damage to the microsphere body, the process is cumbersome and the cost is high; and the spray method is also expensive and not suitable for scale-up production. In addition, there are seed swelling method and porogen method. The seed swelling method forms a porous structure by swelling seed particles, while the porogen method creates pores by adding porogens. However, the diameter size, pore size distribution and specific surface area of hollow porous microspheres prepared by different porogens are different, and the dispersion of microsphere diameters also varies.
[0005] In order to solve the problems in the prior art that the pore-making effect of polyurethane hollow microspheres is poor and the shape and size are difficult to control, the present application provides a hollow porous microsphere and a preparation method thereof. Summary of the invention
[0006] The present invention provides a hollow porous microsphere and a preparation method and application thereof, so as to overcome the problems in the prior art of poor pore making effect and difficulty in controlling the morphology and size. The hollow porous microsphere of the present invention has a high loading amount of coupled macromolecules and a magnetic content, which is beneficial to its application in chemiluminescent immunodiagnosis cell sorting and nucleic acid purification.
[0007] The specific technical solutions are as follows:
[0008] One of the purposes of the present invention is to provide a method for preparing hollow porous microspheres, comprising the following steps:
[0009] 1) Isocyanate reacts with polyethylene glycol in a solvent to obtain a prepolymer;
[0010] 2) reacting the prepolymer with a hydroxyl functional monomer to obtain a waterborne polyurethane;
[0011] 3) mixing the waterborne polyurethane, polymerization monomer, porogen and initiator to obtain an organic phase; mixing the organic phase with water, reacting, separating and drying to obtain the hollow porous microspheres.
[0012] The present invention prepares a nonionic waterborne polyurethane (WPU) with double bonds and PEG blocks by using isocyanate, polyethylene glycol and hydroxyl-containing functional monomers. The nonionic waterborne polyurethane can use itself as an emulsifier and polymerize monomers to obtain hollow porous microspheres through self-emulsification-self-polymerization reactions.
[0013] In certain embodiments, in step 1), the isocyanate is selected from one or more of isophorone diisocyanate (IPDI), toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI) and hexamethylene diisocyanate (HDI). Preferably, it is isophorone diisocyanate (IPDI).
[0014] In certain embodiments, in step 1), the molecular weight of the polyethylene glycol is 2000 to 5000. The molecular weight of polyethylene glycol in this application refers to the average molecular weight. This application studies the alcohols for synthesizing waterborne polyurethanes and finds that the hollow microspheres prepared by polybutylene glycol, which is commonly used in synthesizing polyurethanes, have poor hydrophilic properties and are difficult to self-emulsify into spheres, while polyethylene glycol can form spheres; further studies were conducted on the molecular weight of polyethylene glycol and found that the particle size of the hollow porous microspheres formed increases with the increase in the molecular weight of polyethylene glycol. When the molecular weight of polyethylene glycol is 2000, the particle size of the hollow porous microspheres is above 1 μm.
[0015] In certain specific embodiments, in step 1), the mass ratio of the polyethylene glycol to the isocyanate is (1-10):1, or (1-4.4):1, or (2.8-6.7):1, or (5.1-10):1, such as 2:0.44.
[0016] In certain embodiments, in step 1), the solvent is toluene.
[0017] In certain embodiments, in step 1), the reaction temperature is 60-80°C, or 60-75°C, or 70-90°C, such as 75°C.
[0018] In certain embodiments, in step 1), the reaction time is 2 to 48 hours, or 1 to 24 hours, or 20 to 48 hours, such as 6 hours.
[0019] In certain embodiments, in step 1), a catalyst is further added, and the catalyst is selected from dibutyltin dilaurate.
[0020] In some specific embodiments, the mass ratio of the cyanate ester to the catalyst is (10-30):1, or (0.05-5):1, or (4-8):1. In one example, it is 1:22.
[0021] In certain embodiments, in step 2), the hydroxyl functional monomer is selected from hydroxyethyl methacrylate (HEMA). In the present application, hydroxyethyl methacrylate can introduce double bonds and hydroxyl functional groups at the end of the polyurethane chain, and the double bonds in HEMA can cross-link with the polymerized monomer during the polymerization process to form a network structure.
[0022] In certain specific embodiments, in step 2), the molar ratio of the isocyanate group in the isocyanate to the hydroxyl group in the hydroxyl-containing functional monomer is 1 to 3. In the present application, the molar ratio of the isocyanate group in the isocyanate to the hydroxyl group in the hydroxyl-containing functional monomer (i.e., R value) should not be too high or too low. If it is too high, the proportion of isocyanate will be too high, the cost will increase significantly, and it is not suitable for scale-up production; if the molar ratio is less than 1, the molecular weight of the prepolymer obtained by the reaction will be too low, and only dimers or trimers can be formed, not polymers, and microspheres cannot be formed, which will affect the performance.
[0023] In certain embodiments, in step 2), the reaction temperature is 60-80°C, or 60-75°C, or 70-90°C, such as 75°C.
[0024] In certain embodiments, in step 2), the reaction time is 2 to 48 hours, or 1 to 24 hours, or 20 to 48 hours, such as 6 hours.
[0025] In certain embodiments, in step 3), the solid content of the waterborne polyurethane is 20-30%. The waterborne polyurethane is diluted with a solvent until the solid content of the waterborne polyurethane in the diluent is 20-30%, and the solvent is selected from toluene. The present application found that the solid content should not be too high or too low. If it is too high, the proportion of the polyurethane component is too high, the viscosity of the solution system is too large, the phase transition resistance increases, the difficulty of balling increases or solid microspheres are formed; if it is too low, the shell of the microsphere is too thin and the rigidity is insufficient, causing the microsphere structure to collapse. The solid content is determined as the percentage change in mass of the waterborne polyurethane after heating in a blast drying oven at 120°C for 4 hours. Specifically, ① the weighing bottle records its mass to an accuracy of 0.001g, recorded as m1. ② Weigh the waterborne polyurethane and place it in a weighed weighing bottle, record the weight of WPU to an accuracy of 0.001g, recorded as m2. ③ Put the weighing bottle with the waterborne polyurethane into a blast drying oven at a temperature of 120°C and heat it for 4 hours. ④After the test time is up, take out the glass bottle, put it in a desiccator and cool it to room temperature, weigh its mass to an accuracy of 0.001g, recorded as m3. ⑤Calculate the solid content of waterborne polyurethane according to the following formula, accurate to 0.01%, solid content = (m3-m1) / m2*100%.
[0026] In some embodiments, in step 3), the polymerizable monomer is selected from styrene. The present application has found that using styrene as a polymerizable monomer can provide a certain rigidity to the microspheres because its molecule itself has a rigid benzene ring, thereby better ensuring that the microsphere skeleton will not collapse.
[0027] In some specific embodiments, in step 3), the mass ratio of the polymerizable monomer to the waterborne polyurethane is (0.05-5):1, or (0.05-2):1, or (1-5):1. In one example, it is 0.5:1.
[0028] In certain embodiments, in step 3), the porogen is selected from one or more of toluene, cyclohexane, n-butanol, isopropanol and N,N-dimethylformamide. In certain specific embodiments, the porogen is a combination of cyclohexane and toluene, wherein the volume ratio of cyclohexane to toluene is 1:(1-5), such as 1.18:4; or a combination of n-butanol and toluene, wherein the volume ratio of n-butanol to toluene is 1:(1-5), such as 1.24:4; or a combination of N,N-dimethylformamide (DMF) and toluene, wherein the volume ratio of n-butanol to toluene is 1:(1-5), such as 1.44:4.
[0029] In certain specific embodiments, in step 3), the mass ratio of the porogen to the aqueous polyurethane is (0.05-8):1, or (0.05-5):1, or (4-8):1, such as 4:1.
[0030] In certain embodiments, in step 3), the initiator is selected from azobisisobutyronitrile.
[0031] In certain specific embodiments, in step 3), the mass ratio of the initiator to the aqueous polyurethane is (0.001-0.2):1, or (0.001-0.12):1, or (0.08-0.2):1, such as 0.02:1.
[0032] In certain embodiments, in step 3), the reaction temperature is 60-90°C, or 60-75°C, or 70-90°C, such as 70°C.
[0033] In certain embodiments, in step 3), the reaction time is 1 to 48 hours, or 1 to 24 hours, or 20 to 48 hours, such as 16 hours.
[0034] In certain embodiments, in step 3), the drying temperature is 100-140°C, or 100-110°C, or 100-120°C, or 110-140°C, such as 120°C.
[0035] In certain embodiments, in step 3), the drying time is 30 to 60 hours, or 30 to 45 hours, or 40 to 55 hours, or 50 to 60 hours, such as 48 hours.
[0036] In certain embodiments, in step 3), the separation method is suction filtration.
[0037] In certain embodiments, in step 3), the separation further includes washing to remove impurities attached to the surface of the hollow porous microspheres, such as residual monomers, catalysts, etc.
[0038] In some specific embodiments, ethanol is used for washing.
[0039] The second aspect of the present invention protects the hollow porous microspheres obtained by the preparation method as described above.
[0040] In certain embodiments, the hollow porous microspheres include a shell layer having a hollow structure, the shell layer is a porous structure, and the thickness of the shell layer is 200-300 nm; the particle size of the hollow porous microspheres is 1-3 μm, and the pore size of the porous structure is 1-20 nm.
[0041] The third aspect of the present invention protects the use of the hollow porous microspheres as described above as raw materials in immunomagnetic spheres, which are used for chemiluminescent immunodiagnosis, cell sorting or nucleic acid purification.
[0042] In certain embodiments, the immunomagnetic spheres comprise the hollow porous microspheres described above.
[0043] In certain embodiments, the immunomagnetic spheres are obtained by nitrifying, magnetizing, coating, and carboxyl-modifying the hollow porous microspheres described above.
[0044] In certain specific embodiments, the preparation method of the immunomagnetic spheres is as follows: i) the porous hollow microspheres described above are nitrated in a mixture of nitric acid and sulfuric acid to obtain porous hollow nitrated microspheres; ii) the porous hollow nitrated microspheres and an iron salt solution react under the action of aqueous ammonia to obtain porous hollow magnetic microspheres; iii) the porous hollow magnetic microspheres, dibutyltin dilaurate and isophorone diisocyanate are subjected to a first reaction, and then hydroxyethyl methacrylate is added for a second reaction to obtain coated microspheres; iv) the coated microspheres, azobisisobutyronitrile and acrylic acid react to obtain carboxyl-modified microspheres.
[0045] Preferably, in i), the weight ratio of the porous hollow microspheres to the mixed solution is 1 g:(7-35) g, or can be, or can be. In a certain embodiment, it is 1:24.
[0046] Preferably, in i), the mass ratio of sulfuric acid to nitric acid is (1-10):1, or (1-5):1, or (4-10):1. In one embodiment, it is 4.8:1.
[0047] Preferably, in i), the temperature of the nitrification treatment is 20-60°C, or 20-42°C, or 40-60°C. In one embodiment, it is 30°C.
[0048] Preferably, in i), the nitrification treatment time is 1 to 24 hours, or 1 to 24 hours, or 20 to 48 hours. In one embodiment, it is 2 hours.
[0049] Specifically, in a certain example, the following steps are included: a mixed solution of 25 g of 95% sulfuric acid and 7.5 g of 65% nitric acid is cooled to 10°C, and then 1 g of porous hollow microspheres is added, and then the temperature is raised to 30°C for reaction for 2 hours to obtain the nitrated porous hollow microspheres. After the reaction, the steps include cooling, filtering, ethanol washing, water washing, and drying.
[0050] Preferably, in ii), the mass ratio of the iron salt in the iron salt solution to the nitrated porous hollow microspheres is (3-15):1, or (3-10):1, or (6-15):1. In one embodiment, it is 10:1.
[0051] Preferably, in ii), the iron salt is selected from ferrous sulfate. In a certain embodiment, it is FeSO4·7H2O.
[0052] Preferably, in ii), the mass concentration of the aqueous ammonia is 1-35wt%, or 1-20wt%, or 15-35wt%. In one embodiment, it is 20wt%.
[0053] Preferably, in ii), the reaction temperature is 40-100°C, or 40-70°C, or 60-100°C. In one embodiment, it is 60°C.
[0054] Preferably, in ii), the reaction time is 1 to 24 hours, or 1 to 24 hours, or 20 to 48 hours. In one embodiment, it is 4 hours.
[0055] Preferably, in ii), the reaction further comprises adding manganese sulfate.
[0056] Specifically, in one embodiment, the method includes the following steps: 1 g of porous hollow nitrated microspheres are dispersed in 10 g of water, and reacted with 10 g of FeSO4·7H2O, 0.02 g of MnSO4·H2O and 10 mL of 25% ammonia water at 60° C. for 4 hours. After the reaction, magnetic separation and washing may also be performed.
[0057] Preferably, in iii), the mass ratio of the porous hollow magnetic microspheres to the dibutyltin dilaurate (DBTDL) is 1:(0.005-0.1), or 1:(0.005-0.05), or 1:(0.04-0.1). In one embodiment, it is 1:0.01.
[0058] Preferably, in iii), the mass ratio of the porous hollow magnetic microspheres to isophorone diisocyanate (IPDI) is 1:(0.2-5), or 1:(0.2-3, or 1:(2-5). In one embodiment, it is 1:1.
[0059] Preferably, in iii), the mass ratio of the porous hollow magnetic microspheres to hydroxyethyl methacrylate (HEMA) is 1:(0.1-1), or 1:(0.1-0.6), or 1:(0.5-1). In one embodiment, it is 1:0.26.
[0060] Preferably, in iii), the temperature of the first reaction is 40-100°C, or 40-70°C, or 60-100°C. In one embodiment, it is 75°C.
[0061] Preferably, in iii), the second reaction time is 1 to 48 hours, or 1 to 24 hours, or 20 to 48 hours. In one embodiment, it is 4 hours.
[0062] Preferably, in iii), the temperature of the second reaction is 40-100°C, or 40-70°C, or 60-100°C. In one embodiment, it is 75°C.
[0063] Preferably, in iii), the first reaction time is 1 to 48 hours, or 1 to 24 hours, or 20 to 48 hours. In one embodiment, it is 6 hours.
[0064] Specifically in one embodiment, the carboxyl modification comprises the following steps: the porous hollow magnetic microspheres are dispersed in acetone, reacted with DBTDL and IPDI for a first reaction, HEMA is added for a second reaction, magnetic separation is performed, and washing is performed to obtain the carboxyl modified porous hollow magnetic microspheres. During the washing, the washing agent used is ethanol or water.
[0065] Preferably, in iv), the mass ratio of the coated sphere to azobisisobutyronitrile (AIBN) is 1:(0.01-0.5), or 1:(0.01-0.3), or 1:(0.2-0.5). In one embodiment, it is 1:0.04.
[0066] Preferably, in iv), the mass ratio of the coated sphere to the acrylic acid is 1:(1-3), or 1:(1-1.8), or 1:(1.5-3). In one embodiment, it is 1:2.
[0067] Preferably, in iv), the reaction temperature is 40-100°C, or 40-60°C, or 50-100°C. In one embodiment, it is 70°C.
[0068] Preferably, in iv), the reaction time is 1 to 48 hours, or 1 to 24 hours, or 20 to 48 hours. In one embodiment, it is 16 hours.
[0069] Preferably, the reaction is carried out in a protective atmosphere selected from nitrogen.
[0070] In a specific example, the carboxyl modification step is: the coated spheres are dispersed in ethanol, reacted with AIBN and acrylic acid, and washed to obtain carboxyl-modified porous hollow magnetic microspheres. During the washing, the detergent used is ethanol or water.
[0071] The hollow porous microsphere core-shell structure of the present invention has a hollow core and a porous shell, and has the advantages of a large specific surface area, a high magnetic content after being loaded with magnetic substances, and a large loading capacity for macromolecules. It can be used as a solid phase carrier for chemiluminescent immunoassay and as an immunomagnetic bead for chemiluminescent immunodiagnosis, cell sorting or nucleic acid purification, etc.
[0072] Compared with the prior art, the present invention has the following beneficial effects:
[0073] 1) The hollow porous microspheres of the present invention are made of non-ionic waterborne polyurethane (WPU) with double bonds and PEG blocks as raw materials, and WPU itself is used as an emulsifier and a polymerization monomer, through a self-emulsification-self-polymerization reaction, and vacuum drying to obtain hollow porous microspheres.
[0074] 2) The hollow porous microspheres of the present invention can be obtained without using a surfactant or an emulsifier, and the subsequent preparation of magnetic microspheres and immunomagnetic beads for chemiluminescent immunodiagnosis is highly safe.
[0075] 3) The hollow porous microspheres of the present invention comprise a hollow core and a porous shell, and are rigid and will not collapse. In addition, they have a large specific surface area, which is conducive to subsequent use as magnetic microspheres and immunomagnetic beads to adsorb and separate macromolecules, such as proteins.
[0076] 4) The hollow porous microspheres of the present invention are used as raw materials for magnetic microspheres and immunomagnetic beads, and their coupling with antibodies, proteins, etc. can achieve higher loading capacity and higher magnetic content. BRIEF DESCRIPTION OF THE DRAWINGS
[0077] Figure 1 This is a graph showing the effects of different porogens on the morphology of hollow porous microspheres WPUMs in the present invention.
[0078] Figure 2 This is a graph showing the effect of different solid contents on the morphology of hollow porous microspheres WPUMs in the present invention.
[0079] Figure 3 This is the TSH standard curve in Example 2 of the present invention. DETAILED DESCRIPTION
[0080] The present invention will be further described below in conjunction with specific embodiments. The following are only specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto.
[0081] Example 1
[0082] In this Example 1, the synthesis of waterborne polyurethane with different molecular weights and different types of diols was studied. It includes the following:
[0083] 1) Take 2 g of diols of different types and molecular weights in Table 1 and 0.02 g of catalyst dibutyltin dilaurate, dissolve them in 10 g of toluene, add them into a three-necked flask with a mechanical stirrer, set the stirrer speed to 250 rpm, pass nitrogen for 30 minutes, set the temperature to 75°C, add 0.44 g of isophorone diisocyanate (IPDI), react at 75°C for 4 hours to obtain a prepolymer.
[0084] 2) Then, 0.26 g of hydroxyl functional monomer hydroxyethyl methacrylate (HEMA) was added and reacted at 75°C for 6 hours. After the reaction, waterborne polyurethane (WPU) was obtained. The waterborne polyurethane (WPU) was then diluted with toluene to a solid content of 20% and stored for later use to obtain a toluene solution of WPU.
[0085] 3) Take the toluene solution (about 5 g solution) containing 1 g WPU obtained in step 2), add 0.5 g of polymerization monomer styrene, mix well, add to a three-necked flask containing 0.02 g of initiator azobisisobutyronitrile (AIBN), set the stirrer speed to 1500 rpm, and pass nitrogen for 30 minutes to obtain an organic phase; then quickly add 10 g of pure water to the organic phase, stir and mix for 30 minutes, after stirring, set the temperature to 70 ° C, adjust the speed to 200 rpm, and react for 16 hours to polymerize into balls. After the reaction is completed, filter and obtain a white solid, wash with anhydrous ethanol, filter, repeat 3 times, and put it into a vacuum drying oven at 120 ° C. After drying for 48 hours, store it for use to obtain hollow microspheres.
[0086] Then, the particle size of the hollow microspheres obtained from diols of different molecular weights and different types was tested using a Backman Coulter LS 320 laser particle size analyzer. The results are shown in Table 1.
[0087] R value calculation: Calculated according to the formula ,in n -NCO is the molar amount of isocyanate, n -OH is the molar amount of hydroxyl groups.
[0088] Table 1 Effects of different types and molecular weights of diols on the particle size of hollow microspheres
[0089]
[0090] As shown in Table 1, the hollow microspheres prepared by using polytetramethylene glycol (PTMG), which is mainly used to produce polyurethane in the prior art, are difficult to self-emulsify into spheres due to the poor hydrophilicity of PTMG and insufficient self-emulsification ability, thus causing agglomeration. When hollow microspheres are prepared by using polyethylene glycol (PEG) as a raw material, evenly dispersed hollow microspheres can be formed, and as the molecular weight of PEG (from 200 to 5000) increases, the particle size of the hollow microspheres also increases. Considering the subsequent application as immunomagnetic beads, the particle size of the hollow microspheres prepared by PEG2000 is appropriately selected for the next experiment.
[0091] Example 2
[0092] In this Example 2, the pore-forming effects of different porogens on hollow microspheres are investigated, including the following:
[0093] 1) Take 2 g of PEG2000 and 0.02 g of catalyst dibutyltin dilaurate, dissolve them in 10 g of toluene, add them to a three-necked flask with a mechanical stirrer, set the stirrer speed to 250 rpm, pass nitrogen for 30 minutes, set the temperature to 75°C, add 0.44 g of isophorone diisocyanate (IPDI), react at 75°C for 4 hours to obtain a prepolymer.
[0094] 2) Then, 0.26 g of hydroxyl functional monomer hydroxyethyl methacrylate (HEMA) was added and reacted at 75°C for 6 hours. After the reaction, waterborne polyurethane (WPU) was obtained. The waterborne polyurethane (WPU) was then diluted with toluene to a solid content of 20% and stored for later use to obtain a toluene solution of WPU.
[0095] 3) Take the toluene solution containing 1 g of WPU obtained in step 2), add 0.5 g of polymerized monomer styrene and the porogen in Table 2, mix well, add to a three-necked flask containing 0.02 g of initiator azobisisobutyronitrile (AIBN), set the stirrer speed to 1500 rpm, and after nitrogen is passed for 30 minutes, an organic phase is obtained; then 10 g of pure water is quickly added to the organic phase, stirred for 30 minutes, and after the end, the temperature is set to 70°C, the speed is adjusted to 200 rpm, and the reaction is carried out for 16 hours. After the reaction is completed, filter and obtain a white solid, wash with anhydrous ethanol, filter, repeat 3 times, put into a vacuum drying oven at 120°C, dry for 48 hours, and obtain hollow porous microspheres, which are stored for later use.
[0096] Surface morphology test of hollow porous microspheres: Then, the surface morphology of the hollow porous microspheres obtained in step 3) of this embodiment was analyzed using a JSM-6380LV scanning electron microscope of Japan Co., Ltd. The results are shown in FIG. Figure 1 Among them, A1 / A2 represents microspheres prepared from porogen cyclohexane and toluene; B1 / B2 represents microspheres prepared from porogen toluene; C1 / C2 represents microspheres prepared from porogen n-butanol and toluene; D1 / D2 represents microspheres prepared from porogen DMF and toluene). The left column is the SEM image of 100nm, and the right column is the SEM image of 0.5μm.
[0097] Solid content test: ① Take a clean and dry glass weighing bottle and record its mass to an accuracy of 0.001g, recorded as m1. Peel the analytical balance. ② Weigh a certain mass of the toluene solution of WPU in step 2) of this embodiment, place it in a weighed glass weighing bottle, and record the weight of WPU to an accuracy of 0.001g, recorded as m2. ③ Put the glass bottle containing the toluene solution of WPU into a blast drying oven at a temperature of 120°C and heat it for 4 hours. ④ After the test time is reached, take out the glass bottle, put it in a dryer and cool it to room temperature, weigh its mass to an accuracy of 0.001g, recorded as m3. ⑤ Calculate the solid content of the WPU solution according to the following formula to an accuracy of 0.01%.
[0098] WPU solution 固含量 = (m3-m1) / m2*100%
[0099] Chemiluminescence performance test: The hollow porous microspheres formed by different porogens and solvents obtained in step 3) are sequentially subjected to nitration treatment, magnetization treatment, coating, and carboxyl modification to obtain composite magnetic microspheres (i.e., immunomagnetic microspheres). The magnetic content of the composite magnetic microspheres is measured. The composite magnetic microspheres are then subjected to chemiluminescence performance test to determine their adsorption amount of macromolecules.
[0100] The preparation method of composite magnetic microspheres comprises the following steps:
[0101] 1) Nitration treatment: A mixture of 25 g of 95% sulfuric acid and 7.5 g of 65% nitric acid was cooled to 10°C, and then 1 g of each hollow porous microsphere was added. The temperature was raised to 30°C and stirred at 250 rpm for 2 hours. Then, 150 g of ice water was added. Filter, wash with ethanol 3 times, and then wash with pure water 3 times, and dry to obtain hollow porous nitrated microspheres.
[0102] 2) Magnetization treatment: Take 1 g of hollow porous nitrated microspheres, disperse them with 10 g of pure water, add them to a three-necked flask containing 10 g of FeSO4·7H2O and 0.02 g of MnSO4·H2O, start stirring, and pass nitrogen at 250 rpm for 30 minutes. Raise the temperature to 60°C, add 10 mL of 25% ammonia water, and react at 60°C for 4 hours to magnetize. Magnetic separation, wash and disperse with pure water to obtain a dispersion containing hollow porous magnetized microspheres. Determine the solid content of the dispersion and save it for later use.
[0103] 3) Coating: Take 1 g of porous hollow magnetized microspheres, magnetically separate, wash with acetone three times, then disperse with 10 g of acetone, add to a three-necked flask containing 0.01 g DBTDL and 1 g IPDI, set the stirrer speed to 250 rpm, pass nitrogen for 30 minutes, raise the temperature to 75°C, react at 75°C for 4 hours, add 0.26 g HEMA, react at 75°C for 6 hours, after completion, magnetically separate, wash with ethanol three times, wash with pure water three times, disperse with pure water to obtain coated spheres.
[0104] 4) Carboxyl modification: Take 1 g of coated magnetic balls, separate magnetically, wash with ethanol three times, then disperse with 10 g of ethanol, add to a three-necked flask containing 0.04 g AIBN and 2 g acrylic acid, set the stirrer speed to 250 rpm, pass nitrogen for 30 minutes, raise the temperature to 70°C, react at 70°C for 16 hours, and after completion, wash with ethanol three times, wash with pure water three times, disperse with pure water, measure the solid content, and store for later use to obtain carboxyl-modified magnetic beads.
[0105] 5) Immobilization of streptavidin:
[0106] i) Take 10 mg of carboxyl-modified magnetic beads, separate them by magnetic separation, remove the supernatant, wash them three times with MES, pH 6.0, and add 1 mg of streptavidin dissolved in 900 μL MES, pH 6.0, to the magnetic beads.
[0107] ii) The mixed dispersion of magnetic beads and streptavidin was incubated at room temperature for 30 minutes using a mixing device.
[0108] iii) Weigh 1 mg of EDC, dissolve it in 100 μL of pH 6.0 MES, add it to the mixed dispersion, and react at room temperature for 5 hours.
[0109] iv) Magnetic separation, remove the supernatant, wash three times with pH 7.4 phosphate buffer containing 0.01% (W / V) Tween-20 to remove excess EDC and streptavidin, and finally disperse with 1 mL of pH 7.4 phosphate buffer containing 0.01% (W / V) Tween-20 to obtain composite magnetic microspheres, which are stored at 2-8°C for future use.
[0110] Magnetic content determination: The solid content data of the dispersion after magnetization (C 固含量 )、Total mass of dispersion after magnetization (m a ) and the mass of porous hollow nitrified microspheres (m b ), the magnetic content is calculated according to the following formula, accurate to 0.01%.
[0111]
[0112] Among them, the solid content data (C 固含量 ) is the solid content of the dispersion in step 2), %; the total mass of the dispersion after magnetization (m a ) is the total mass of the dispersion in step 2), g; the mass of the nitrifying ball (m b ) is the feeding amount of porous hollow nitration microspheres in step 2).
[0113] Magnetic content (%) refers to the percentage of the mass of magnetic material in magnetic microspheres to the mass of the entire microspheres. It is a key indicator for measuring the magnetic properties of magnetic microspheres and directly affects the magnetization intensity and magnetic response performance of magnetic microspheres.
[0114] Antibody adsorption test: The adsorption amount of TSH by composite magnetic microspheres:
[0115] 1) In this experiment, TSH was selected as the representative antibody of IgG subtype, and the adsorption capacity of composite magnetic microspheres to antibodies was determined by Lowry method using a multifunctional microplate reader. Reagent A refers to the standard configuration of Folin phenol methyl reagent A: Folin phenol methyl reagent B = 50:1, and Folin phenol methyl reagent is provided by the kit; Reagent B refers to Folin phenol ethyl reagent, which is provided by the kit.
[0116] 2) Determination of TSH standard curve: Prepare TSH antibody solutions with concentration gradients of 0 mg / mL, 0.01 mg / mL, 0.02 mg / mL, 0.05 mg / mL, 0.1 mg / mL, 0.15 mg / mL, 0.2 mg / mL, 0.25 mg / mL, and 0.4 mg / mL. Use a 96-well plate equipped with an ELISA reader to transfer different concentrations of TSH antibody solutions with a pipette. Repeat the wells and transfer 200 μL of reagent A to each sample well with a pipette. Mix and shake for 30 seconds and let stand for 10 minutes. Use a pipette to transfer 20 μL of reagent B to each well, mix and shake for 30 seconds, and then place in a 37°C air drying oven for constant temperature incubation for 30 minutes.
[0117] 3) After the incubation, the corresponding absorbance is obtained at A650, the absorbance at 0 mg / mL (background value) is deducted, the average value is taken, and the standard curve and formula are fitted, as shown below: Figure 3 shown.
[0118] 4) Determination of TSH adsorption by composite magnetic microspheres: Take 10 mg of composite magnetic microsphere powder, disperse it with 1 mL of MES buffer at pH = 6.0, add 1 mg of TSH, dissolve and shake well, shake at room temperature for 16 hours, centrifuge, and take the supernatant for testing. Use a pipette to add 20 μL of MES solution and supernatant to be tested, duplicate wells, and pipette 200 μL of reagent A to each sample well, mix and shake for 30 seconds, and let it stand for 10 minutes. Use a pipette to add 20 μL of reagent B to each well, mix and shake for 30 seconds, and then incubate in a 37 ℃ constant temperature drying oven for 30 minutes.
[0119] The absorbance of A650 of each sample well was tested with a multifunctional microplate reader, and the average value was taken to obtain the absorbance (A1) and background value (A0) of the supernatant to be tested.
[0120] After the test, record the absorbance value and calculate the surface antibody adsorption amount C of the corresponding composite magnetic microspheres. Ab , the unit is [mg / g], the calculation formula is as follows, and the result is shown in Figure 2.
[0121]
[0122] Table 2 Effects of different porogens on the morphology of hollow porous microspheres, magnetic content of porous hollow magnetized microspheres, and adsorption of TSH antibody by composite magnetic microspheres
[0123]
[0124] From Table 2 and Figure 1 It can be seen that the polarity of the porogen and the solubility parameters of the combination formed by different porogens will jointly affect the porous morphology of the surface of the hollow porous microspheres. The smaller the polarity of the porogen, the rougher the surface morphology of the obtained hollow porous microspheres and the larger the pores on the surface; the larger the solubility parameter of the combination, the smoother the surface of the obtained hollow porous microspheres, but the smaller the pore size, and the denser. At the same time, it can be seen from Table 2 that the hollow porous microspheres obtained by using toluene as a porogen have the largest specific surface area, the highest magnetic content, and the highest TSH antibody adsorption amount, so toluene is selected as a porogen and toluene as a solvent.
[0125] Example 3
[0126] In this Example 3, the effects of different solid contents of waterborne polyurethane on hollow porous microspheres are investigated. The results are as follows:
[0127] 1) Take 2 g of PEG2000 and 0.02 g of catalyst dibutyltin dilaurate, dissolve them in 10 g of toluene, add them into a three-necked flask with a mechanical stirrer, set the stirrer speed to 250 rpm, pass nitrogen for 30 minutes, set the temperature to 75°C, add 0.44 g of isophorone diisocyanate (IPDI), react at 75°C for 4 hours to obtain a prepolymer;
[0128] 2) Then, 0.26 g of hydroxyl functional monomer hydroxyethyl methacrylate (HEMA) was added and reacted at 75°C for 6 hours. After the reaction, waterborne polyurethane (WPU) was obtained. Then, the waterborne polyurethane (WPU) was diluted with toluene to the solid content in Table 3 and stored for later use to obtain a toluene solution of WPU.
[0129] 3) Take a toluene solution containing 1 g of WPU, add 0.5 g of polymerized monomer styrene and 4 g of toluene, mix well, add to a three-necked flask containing 0.02 g of initiator azobisisobutyronitrile (AIBN), set the stirrer speed to 1500 rpm, and after nitrogen is passed for 30 minutes, an organic phase is obtained; then 10 g of pure water is quickly added to the organic phase, stirred for 30 minutes, and after the end, the temperature is set to 70°C, the speed is adjusted to 200 rpm, and the reaction is carried out for 16 hours. After the reaction is completed, filter and obtain a white solid, wash with anhydrous ethanol, filter, repeat 3 times, put it in a vacuum drying oven at 120°C, dry it for 48 hours, and obtain hollow porous microspheres, which are stored for later use.
[0130] Hollow morphology test of hollow porous microspheres: Then the internal structure of hollow porous microspheres was analyzed using a JEM-2100F field emission transmission electron microscope from Japan Co., Ltd. Figure 2 Among them, a represents the hollow porous microspheres prepared by WPU-6; b represents the hollow porous microspheres prepared by WPU-7; c represents the hollow porous microspheres prepared by WPU-8; d represents the hollow porous microspheres prepared by WPU-9.
[0131] Solid content test: same steps as in Example 2, the results are shown in Table 3.
[0132] Particle size test: The particle size of the hollow porous microspheres obtained in step 3) of this embodiment was tested using a Backman Coulter LS 320 laser particle size analyzer. The results are shown in Table 3.
[0133] Specific surface area test: The specific surface area of the hollow porous microspheres obtained in step 3) of this embodiment was analyzed by nitrogen adsorption-desorption using an ASAP 2020 M fully automatic physical adsorption instrument from Micromeritics, USA.
[0134] The aqueous polyurethane with different solid contents obtained in this example was used to form composite magnetic microspheres, and the steps were the same as those in Example 2. Then, the magnetic content of the obtained porous hollow magnetized microspheres and the TSH antibody adsorption of the obtained composite magnetic microspheres were measured, and the measurement methods were the same as those in Example 2. The results are shown in Table 3.
[0135] Table 3 Effect of different solid contents on microsphere morphology
[0136]
[0137] From Table 3 and Figure 2 It can be seen that the solid content of the toluene solution of WPU directly affects the hollow structure of the hollow porous microspheres. If the solid content is too high, the proportion of the polyurethane component in the toluene solution of WPU is too high, the viscosity of the solution system is too large, the phase transition resistance increases, and the difficulty of ball formation increases. When the solid content is reduced to 40%, although it can be balled, it is a solid microsphere with a non-hollow morphology. When the solid content is further reduced, the viscosity decreases further, the activation energy required for the phase transition decreases, and there is enough toluene as a soft template to provide space in the cavity of the hollow porous microsphere. After removing the toluene, a hollow structure is formed, and the shell becomes thinner as the solid content decreases. When it drops to 10%, the shell of the microsphere is too thin and insufficiently rigid, causing the microsphere structure to collapse. Therefore, the suitable solid content is 20-30%.
[0138] Comparative Example 1
[0139] Solid porous microspheres were prepared in Comparative Example 1. They include the following:
[0140] 1) Take 2 g of PEG2000 and 0.02 g of catalyst dibutyltin dilaurate, dissolve them in 10 g of toluene, add them into a three-necked flask with a mechanical stirrer, set the stirrer speed to 250 rpm, pass nitrogen for 30 minutes, set the temperature to 75°C, add 0.44 g of isophorone diisocyanate (IPDI), react at 75°C for 4 hours to obtain a prepolymer;
[0141] 2) Then, 0.26 g of hydroxyl functional monomer hydroxyethyl methacrylate (HEMA) was added and reacted at 75°C for 6 hours. After the reaction, waterborne polyurethane (WPU) was obtained. The waterborne polyurethane (WPU) was then diluted with toluene to a solid content of 40% and stored for later use to obtain a toluene solution of WPU.
[0142] 3) Take the toluene solution containing 1 g of WPU obtained in step 2), add 0.5 g of polymerized monomer styrene and 4 g of toluene, mix well, add to a three-necked flask containing 0.02 g of initiator azobisisobutyronitrile (AIBN), set the stirrer speed to 1500 rpm, and after nitrogen is passed for 30 minutes, an organic phase is obtained; then 10 g of pure water is quickly added to the organic phase, stirred for 30 minutes, and after the end, the temperature is set to 70°C, the speed is adjusted to 200 rpm, and the reaction is carried out for 16 hours. After the reaction is completed, filter to obtain a white solid, wash with anhydrous ethanol, filter, repeat 3 times, put into a vacuum drying oven at 120°C, dry for 48 hours, and obtain solid porous microspheres, which are stored for later use.
[0143] The hollow porous microspheres of Example 3 and the solid porous microspheres obtained in Comparative Example 1 were nitrated and magnetized to obtain hollow porous magnetized microspheres and solid porous magnetized microspheres, respectively; the feed ratio of the porous nitrated microspheres and ferrous sulfate in the magnetization treatment is shown in Table 4, and the rest of the preparation methods are the same as those in Example 2.
[0144] Furthermore, the hollow porous magnetized microspheres obtained in Example 3 and the solid porous magnetized microspheres obtained in Comparative Example 1 were coated, carboxyl modified, and streptavidin fixed to obtain hollow porous composite magnetic microspheres and solid porous composite microspheres, respectively; the free biotin binding amount was tested and the magnetic bead double antibody sandwich method was used to detect thyrotropin, respectively; the rest was the same as in Example 2.
[0145] Test of free biotin binding amount: The free biotin binding amount of SA on the microsphere surface was quantified by the biotinylated fluorescein (B4F) method using the TECAN Infinite200Pro multifunctional microplate reader. The unit is pmol / mg. The formula is as follows.
[0146]
[0147] Where F0 is the fluorescence intensity of 10 nmol / ml B4F in PBS (excitation wavelength is 490 nm, emission wavelength is 525 nm), F1 is the fluorescence intensity of the supernatant solution after the microspheres to be tested reacted with 1 ml of 10 nmol / ml B4F in PBS at room temperature for 1 h (excitation wavelength is 490 nm, emission wavelength is 525 nm), m is the mass of magnetic beads in step 1.6.
[0148] Specific steps: Take 6 mg of each of the hollow porous immunomagnetic microspheres and solid porous immunomagnetic microspheres to be tested, take 3 mg respectively and add them to two 2 mL EP tubes, magnetically separate, remove the supernatant, add 1 mL of 50mM pH=7.4 PBS buffer respectively, and shake well. Take one tube for solid-liquid separation, remove the supernatant, repeat 3 times, then add 1 mL10nmol / ml B4F solution, shake well, wrap the outside of the EP tube with aluminum foil to completely avoid light, and react at room temperature on a rotary mixer for 2 hours. The other tube is not treated separately, the outside of the EP tube is wrapped with aluminum foil to completely avoid light, and react at room temperature on a rotary mixer for 2 hours as a control. After the reaction, perform magnetic separation, take out 200 μL of the supernatant, add it to a black 96-well ELISA plate at a volume of 200 μL / well, set the multifunctional ELISA reader to an excitation wavelength of 490 nm, an emission wavelength of 525 nm, and a Gain value of 50, repeat the test twice, take the average value, and substitute it into the following formula to calculate the biotin binding amount of the SA magnetic beads.
[0149] The detection of TSH is the same as in Example 2.
[0150] The magnetic content and magnetic response time of the hollow porous magnetized microspheres of Example 3 and the solid porous magnetized microspheres of Comparative Example 1 were tested. The results are shown in Table 4.
[0151] The test results of free biotin binding amount of the hollow porous composite magnetic microspheres of Example 3 and the solid porous composite magnetic microspheres of Comparative Example 1 are shown in Table 5, and the TSH test results are shown in Table 6.
[0152] Table 4
[0153]
[0154] As can be seen from Table 4, under the same feed ratio, the hollow porous microspheres of the present application obtained after nitration and magnetization have a higher magnetic content, which is more than 1.5 times that of the solid porous magnetized microspheres, and the magnetic content tends to the upper limit at a feed ratio of 15 times, and the magnetic content is as high as 95.2%; while the solid porous microspheres of Comparative Example 1 obtained after nitration and magnetization have a magnetic content that tends to the upper limit at a feed ratio of 10 times, and the magnetic content is only 47%. Under the same feed ratio, the magnetic response time of the hollow porous microspheres of the present application after nitration and magnetization is about half of that of Comparative Example 1, and the magnetic response time tends to the upper limit at a feed ratio of 15 times, t 50 is 17.6 s; however, after the solid porous microspheres of Comparative Example 1 were nitrated and magnetized, the magnetic response time tended to the upper limit at a 10-fold feed ratio, t 50 It is 77.9 s. This shows that after nitration and magnetization, the hollow porous microspheres of the present application have a higher magnetic content and a shorter magnetic response time due to their hollow structure.
[0155] Table 5
[0156]
[0157] Because the magnetic content was too little and the magnetic response time was too long when the FeSO4•7H2O / nitrification ball feed ratio was 3:1 in Comparative Example 1, the subsequent free biotin binding amount was only determined with feed ratios of 6:1 and 10:1.
[0158] It can be seen from Table 5 that the free biotin binding amount of the hollow porous composite magnetic microspheres formed by the hollow porous microspheres is 3 times that of Example 1, which further verifies that the hollow porous morphology of the present application not only has a significant advantage in improving the magnetic content, but also has a higher upper limit in the capacity of loading protein.
[0159] Table 6
[0160]
[0161] Furthermore, because in Comparative Example 1, when the FeSO4•7H2O / nitrification ball feed ratio was 10:1, the magnetic content was too little and the magnetic response time was too long, and the free biotin binding amount was small, the TSH test was carried out when the feed ratio was 6:1.
[0162] It can be seen from Table 6 that when the hollow porous microspheres of the present application are tested for TSH, even when the feed ratio is 15:1, the signal value is still lower than that of Comparative Example 1, indicating that the background value of the hollow porous microspheres of the present application is low, there is no nonspecific adsorption of protein, and the sensitivity is high; in addition, when the feed ratio is 3:1, the signal value of the present application is 3-4 times that of 15:1, and the sensitivity is also increased by nearly 2 times, which also illustrates the decrease in the natural advantage value of the hollow porous microspheres of the present application in chemiluminescent immunoassay.
Claims
1. A method for preparing hollow porous microspheres, characterized in that: The steps include: 1) Isocyanate reacts with polyethylene glycol in a solvent to obtain a prepolymer; 2) reacting the prepolymer with a hydroxyl functional monomer to obtain a waterborne polyurethane; 3) mixing the waterborne polyurethane, polymerization monomer, porogen and initiator to obtain an organic phase; mixing the organic phase with water, reacting, separating and drying to obtain the hollow porous microspheres; In step 2), the hydroxyl functional monomer is selected from hydroxyethyl methacrylate; In step 3), the polymerizable monomer is selected from styrene; In step 3), the solid content of the waterborne polyurethane is 20-30%, and the porogen is selected from one or more of toluene, cyclohexane, n-butanol, isopropanol and N,N-dimethylformamide.
2. The preparation method according to claim 1, characterized in that: The isocyanate is selected from one or more of isophorone diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate and hexamethylene diisocyanate; And / or, the molecular weight of the polyethylene glycol is 2000 to 5000; And / or, the solvent is selected from toluene; And / or, the initiator is selected from azobisisobutyronitrile.
3. The preparation method according to claim 1, characterized in that: The molar ratio of the isocyanate group in the isocyanate to the hydroxyl group in the hydroxyl functional monomer is 1 to 3; And / or, the mass ratio of the polyethylene glycol to the isocyanate is (1-10):1; And / or, the mass ratio of the porogen to the aqueous polyurethane is (0.05-8):1; And / or, the mass ratio of the polymerizable monomer to the aqueous polyurethane is (0.05-5):1; And / or, the mass ratio of the initiator to the aqueous polyurethane is (0.001-0.2):
1.
4. The preparation method according to claim 1, characterized in that: In step 1), the reaction temperature is 60-80°C; And / or, in step 1), the reaction time is 2 to 48 hours; And / or, in step 2), the reaction temperature is 60-80°C; And / or, in step 2), the reaction time is 2 to 48 hours; And / or, in step 3), the reaction temperature is 60-90°C; And / or, in step 3), the reaction time is 1 to 48 hours.
5. The preparation method according to claim 1, characterized in that: Step 1) further comprises adding a catalyst, wherein the catalyst is selected from dibutyltin dilaurate.
6. The preparation method according to claim 5, characterized in that: The mass ratio of the isocyanate to the catalyst is (10-30):
1.
7. The hollow porous microspheres obtained by the preparation method according to any one of claims 1 to 6.
8. The hollow porous microsphere according to claim 7, characterized in that: The hollow porous microspheres include a shell layer with a hollow structure, the shell layer is a porous structure, and the thickness of the shell layer is 200-300 nm; the particle size of the hollow porous microspheres is 1-3 μm, and the pore size in the porous structure is 1-20 nm.
9. Use of the hollow porous microspheres as claimed in claim 7 or 8 as raw materials in the preparation of immunomagnetic spheres, wherein the immunomagnetic spheres are used for chemiluminescent immunodiagnosis, cell sorting or nucleic acid purification, and the use does not belong to a method for diagnosing and treating a disease.
Citation Information
Patent Citations
Preparation method of crosslinked polyurethane microspheres and / or polyurethane hollow microspheres
CN108192074A
Preparation method of polyurethane hollow microspheres
CN108794721A